2022
DOI: 10.3390/biom12060824
|View full text |Cite
|
Sign up to set email alerts
|

NAFLD: Mechanisms, Treatments, and Biomarkers

Abstract: Nonalcoholic fatty liver disease (NAFLD), recently renamed metabolic-associated fatty liver disease (MAFLD), is one of the most common causes of liver diseases worldwide. NAFLD is growing in parallel with the obesity epidemic. No pharmacological treatment is available to treat NAFLD, specifically. The reason might be that NAFLD is a multi-factorial disease with an incomplete understanding of the mechanisms involved, an absence of accurate and inexpensive imaging tools, and lack of adequate non-invasive biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 314 publications
0
135
0
6
Order By: Relevance
“…Therefore, the disease treatment emphasizes the regulation of metabolism, but from clinical practice, there are still several bottlenecks in NAFLD from diagnosis to treatment [9]. Firstly, in terms of diagnosis, although there are more recognized and mature protocols for monitoring NAFLD in traditional high-risk groups (diabetes, hypertension, overweight), more and more studies have found that NAFLD occurs more frequently in people with normal BMI (i.e., visceral obesity) [49], and for such patients, especially in non-obese people with intermittent transaminase abnormalities, there is still a lack of su ciently effective biological markers for the diagnosis of NAFLD and a lack of effective protocols for predicting the risk of development, as liver aspiration biopsy is still not a common tool, and current guidelines only recommend regular follow-up, which is not conducive to timely treatment [50,51]. Secondly, according to the existing guideline recommendations, lifestyle changes, exercise, and diet control are important non-pharmacological options for people with established NAFLD [52].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the disease treatment emphasizes the regulation of metabolism, but from clinical practice, there are still several bottlenecks in NAFLD from diagnosis to treatment [9]. Firstly, in terms of diagnosis, although there are more recognized and mature protocols for monitoring NAFLD in traditional high-risk groups (diabetes, hypertension, overweight), more and more studies have found that NAFLD occurs more frequently in people with normal BMI (i.e., visceral obesity) [49], and for such patients, especially in non-obese people with intermittent transaminase abnormalities, there is still a lack of su ciently effective biological markers for the diagnosis of NAFLD and a lack of effective protocols for predicting the risk of development, as liver aspiration biopsy is still not a common tool, and current guidelines only recommend regular follow-up, which is not conducive to timely treatment [50,51]. Secondly, according to the existing guideline recommendations, lifestyle changes, exercise, and diet control are important non-pharmacological options for people with established NAFLD [52].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological evaluation using liver biopsy is the gold standard for evaluating hepatic steatosis and diagnosing NAFLD, however, this invasive diagnostic modality comes with its limitations including high cost, sampling errors, and post procedure complications [ 8 ]. Hence, multiple studies have investigated several non-invasive modalities for NAFLD diagnosis including potential biomarkers [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…MLXIPL showed a trend of inhibition in the female cohort; however, in males, was upregulated in the 70% versus 0% and 35% bean diets ( Figure 5 b). While SREBF1 is stimulated by insulin (even under conditions of insulin resistance) via mammalian target of rapamycin (mTOR) and by liver X receptor α (LXRα, encoded by Nr1h3 ), MLXIPL signaling is induced by dietary glucose (even more potently by dietary fructose) independently of insulin or dietary fat [ 33 , 34 , 35 ]. Accordingly, we observed inhibition of insulin and its receptor INSR and insulin receptor substrate 1 (IRS-1) based on bean-induced downstream DEGs indicative of improved insulin sensitivity.…”
Section: Resultsmentioning
confidence: 99%